The UK and the European Union Relationships and the Recent ''Brexit'' Implications - Mesbahi, abderraouf (University of Eloued جامعة الوادي, 2018)
تهدف هذه الدراسة إلى استقصاء تاريخ العلاقات التي ربطت المملكة المتحدة والاتحاد الأوربي منذ عقود خلت وذلك بغرض فهم وإعطاء رؤية واضحة تخص قضية بركست الحالية. كما تقوم أيضا هذه الدراسة بمناقشة حدث بركست الحالية وذلك نظرا لكونها قضية الجوهرية في وقتنا هذا. هذا البحث يقوم بدراسة طبيعة العلاقات السابقة بين الجانبين التي انتهت بانفصال بريطانيا عن الاتحاد في استفتاء عام 2016حيث اعتبر انشقاق بريطانيا عن الاتحاد الأوربي حدثا صادما حينها . وفي هذا الصدد تناول البحث فصلين: الفصل الأول يتضمن لمحة عامة عن الاتحاد الأوربي من حيث طبيعة العلاقة التي تربطه بالمملكة المتحدة منذ انضمام بريطانيا عام 1971 إلى غاية عام 2016، كما يسعى للكشف عن المحاور المشتركة للازمات التي وقعت بينهما. أما مسعى الفصل الثاني فكان التطرق لقضية بركست بما في ذلك أسبابها وتداعياتها والإجراءات المتخذة. كما تسعى الدراسة أيضا لقراءة تكهنات العلاقات المستقبلية بين الطرفين.إضافة لذلك تهدف هذه الدراسة إلى لتحقيق بعض المساعي المحددة وهي : تحليل السياسة البريطانية تجاه الاتحاد الأوربي وإيجاد النقاط المشتركة التي ميزت هذه الأزمات الجوهرية وكذالك مناقشة استفتاء بركست والآثار المترتبة عنه. The aim of this study is to explore the history of the relationships between the UK and the EU during the last decades. As a result, we will be able to fully understand the present Brexit issue and to describe it. The study takes the Brexit problem into account and works on discussing it from a different point of view. The main question that was investigated in this work was the nature of the past relationships between the two parts that led eventually to the EU referendum in 2016 and surprisingly to the Brexit and whether the UK is well out of the EU. In this regard, the dissertation is divided into two chapters. The first chapter works on presenting an overview about the EU and then it discusses the nature of the relationship between the UK and the EU since its beginnings in 1971to 2016. It tries also to find points that are common between all the crises that happened. The Second chapter works on covering the Brexit issue including its causes, implications, and procedures. It works also on predicting the future of the relationship between the two sides. The study is intended to reach certain aims which are: providing an analysis of the UK's policy towards the EU and finding the common points that characterized the main crises, discussing the Brexit referendum and its implications.
Keywords: المملكة المتحدة- علاقات- بروكسيت - استفتاء – تداعيات; Brexit, EU, Implications, Referendum, Relationships, UK